Impacto da ansiedade de desempenho durante a disfunção erétil na microbiota intestinal: Estudo de caso - Maiolino, Andréa Barros Ferreira (2024)
Introduction: Significant advances have been made in understanding the complex interactions between the central nervous system, the enteric nervous system, and the gastrointestinal tract. The bidirectional communication between the gut and the brain, known as the gut-brain axis, has increasingly been recognized as a critical component in regulating mood and sexual behavior. Preclinical studies have highlighted the crucial role of the intestinal microbiota in this brain-gut axis, revealing connections between microbial composition and emotional behavior, stress response systems, pain perception, and brain neurotransmitters. Objective: To assess the impact caused by performance anxiety during erectile dysfunction on the intestinal microbiota and how specialized psychotherapeutic intervention in sexual therapy can contribute to restoring erectile function and balance in the intestinal microbiota. Method: Psychotherapy was conducted for the treatment of erectile dysfunction. Before and after the treatment, fecal samples were collected for genomic analysis of the intestinal microbiota using the Shotgun technique. The composition of the intestinal microbiota was investigated at both time points for comparison. The patient responded to three assessment instruments (before and after) via electronic questionnaire: the Hamilton Anxiety Scale, the Erectile Performance Anxiety Index (EPAI), and the International Index of Erectile Function (IIEF) inventory. Results: The results obtained in the initial collection show a possible impact caused by performance anxiety during erectile dysfunction on the intestinal microbiota, including low diversity, increased presence of inflammatory bacteria (Oscillibacter ruminantium and Staphylococcus aureus), and a reduction in anti-inflammatory bacteria (Akkermansia muciniphila and Faecalibacterium prausnitzii). The second collection was performed after sexual psychotherapy and the restoration of erectile function, showing an improvement in the intestinal microbiota with a reduction in inflammatory bacteria (Oscillibacter ruminantium and Staphylococcus aureus) and a significant increase in anti-inflammatory bacteria (Akkermansia muciniphila and Faecalibacterium prausnitzii), along with an increase in microbiota diversity. Conclusion: Thus, this study provides initial evidence of the impact caused by performance anxiety during erectile dysfunction on the intestinal microbiota. It also demonstrates how sexual psychotherapy can be a differential in the treatment and restoration of erectile function, consequently improving the intestinal microbiota, which can impact overall health. It is essential to conduct further studies involving humans to confirm the relevance of the psychological approach in the treatment of erectile dysfunction and, consequently, in the improvement of the intestinal microbiota. This work has immediate practical applicability and provides valuable insights into the complex relationships among mental health, sexual function, and intestinal microbiota. It highlights the importance of sexual psychotherapy as part of a multidisciplinary team in the treatment of erectile dysfunction, considering both physical and emotional factors.